SOLUSI ANALITIK PERSAMAAN TRANSPOR ADVEKSI -DIFUSI 1D DAN 2D HORIZONTAL MENGGUNAKAN TEKNIK TRANSFORMASI FOURIER UNTUK PEMODELAN DISPERSI POLUTAN DI SUATU PERAIRAN - (NIM : 20496005), Aminuddin
Abstract : This thesis discusses analytical solution of 1-D and 2-D horizontal transport equations which has form of - + u.VC = K.4 C. The assumptions are made that velocity u and coefficient of diffusion K are constant. Transport equation in Cartesian coordinate is transformed into Lagrangian coordinate to produce diffusion equation in Lagrangian coordinate system. Fourier transformation technique is then used to get the solution. Analytical solution that is found is in Gaussian form. However, the solutions is undefined for the time and the diffusion coefficient equal to zero, so this solution need to be modified by adding a value of s- = 1 to 4K t term. The modified analytical solution for 1-D and 2-D 7t are applied to simple cases to simulate the pollutant dispersion in a canal/ river and in a rectangular basin. The simulations are performed for instantaneous and continuous sources. Note :Please open the file to see the formulation